2019
DOI: 10.1111/ajo.13053
|View full text |Cite
|
Sign up to set email alerts
|

Impact of service‐wide initiatives to support healthy pregnancy weight gain on weight‐related documentation

Abstract: Background: Excess gestational weight gain is associated with adverse pregnancy outcomes. Addressing barriers to the provision of best practice care that supports healthy pregnancy weight gain could assist staff in clinical care; however, little is known about changes to staff practices after ameliorating barriers. Aims:To evaluate if service initiatives to promote healthy pregnancy weight gain improve weight-related documentation by antenatal staff throughout pregnancy care. Materials and Methods: Service ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Together, this led to better documentation regarding women’s weight [ 41 ] and more women met the IOM guidelines for gestational weight gain [ 71 ]. These findings are in line with other research where changes to the practice environment has improved documentation of weight [ 72 ••] and where changes within electronic medical records show most potential [ 73 ••].…”
Section: Recommendations For Supporting Effective Conversations Regarding Weight Gain With Pregnant Women In Routine Antenatal Caresupporting
confidence: 90%
“…Together, this led to better documentation regarding women’s weight [ 41 ] and more women met the IOM guidelines for gestational weight gain [ 71 ]. These findings are in line with other research where changes to the practice environment has improved documentation of weight [ 72 ••] and where changes within electronic medical records show most potential [ 73 ••].…”
Section: Recommendations For Supporting Effective Conversations Regarding Weight Gain With Pregnant Women In Routine Antenatal Caresupporting
confidence: 90%
“…21,22 Counselling childbearing women who are obese regarding the importance of even modest weight loss may improve their outcomes post CS. 23 This and careful monitoring of gestational weight gain 24 are two strategies that have beneficial effects. It is encouraging to note that a recent Australian study showed women felt informed about the risks and benefits of CS and were satisfied with the decisionmaking process.…”
Section: Discussionmentioning
confidence: 99%
“…7 Face-to-face education for health professionals has been demonstrated to improve knowledge and confidence 20 and improve weight-management practices. [20][21][22] However, access to such training is limited, requires dedicated time and resources and is expensive to scale up, especially in a geographically disperse state such as Queensland. Online training has the potential to be flexible and selfpaced, completed from any location (including rural and remote), undertaken at a time or times convenient to the user, as well as providing a cost-effective and scalable delivery method for the training organisation.…”
Section: Introductionmentioning
confidence: 99%
“…Face‐to‐face education for health professionals has been demonstrated to improve knowledge and confidence 20 and improve weight‐management practices 20–22 . However, access to such training is limited, requires dedicated time and resources and is expensive to scale up, especially in a geographically disperse state such as Queensland.…”
Section: Introductionmentioning
confidence: 99%